2022
DOI: 10.1097/iae.0000000000003438
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Against a Contralateral Coats Phenotype by Optical Coherence Tomography Angiography

Abstract: Purpose: To evaluate the laterality of Coats disease by analyzing optical coherence tomography angiography features in affected, fellow, and control eyes.Methods: Patients with Coats disease who underwent optical coherence tomography angiography were retrospectively reviewed. Healthy eyes of age-matched patients served as controls. Automated optical coherence tomography angiography determination of foveal avascular zone size and vascular density of superficial capillary plexus and deep capillary plexus was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…There are a number of trials that suggest that changes related to FD could progress from the DCP in early disease stages to the SCP in later stages. 9,10 Although the number of cases in our study were small for individual disease stage cohorts, absolute differences in superficial and deep FD between fellow Coats eyes and control eyes seem to be greater in stage 2A than in stage 2B, which may support this assumption.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…There are a number of trials that suggest that changes related to FD could progress from the DCP in early disease stages to the SCP in later stages. 9,10 Although the number of cases in our study were small for individual disease stage cohorts, absolute differences in superficial and deep FD between fellow Coats eyes and control eyes seem to be greater in stage 2A than in stage 2B, which may support this assumption.…”
Section: Discussionmentioning
confidence: 66%
“…However, in stages 1 and 2A, these changes were only observed in the DCP. 10 In their comparative analysis of fellow eyes of Coats patients with healthy control eyes, the authors neither report any differences for FAZ, nor for FD parameters.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have demonstrated that this condition is typically unilateral, and the fellow eye appears normal upon examination with optical coherence tomography (OCT). [17].…”
Section: Discussionmentioning
confidence: 99%